Treatment of Ocular Surface Squamous Neoplasia with Interferon Alpha-2b - Siddiqui, Zahid Kamal; Ahmad, Farooq; Huma, Farah; Tarar, Shahid; Yaqoob, Amir (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the efficacy and safety and of Interferon (IFN) alpha 2b for Ocular Surface Squamous Neoplasia (OSSN). Study Design: Non - Comparative Interventional Study. Place of Study: Mayo Hospital Lahore, Lahore General Hospital, Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan Duration of Study: study was conducted between the period of October 2010 to August 2016. Material and methods: Patients with suspected conjunctival growth underwent incisional biopsy after admission from out patient department. After confirming the diagnosis of Ocular Surface Squamous Neoplasia (OSSN), on Histopathology, case was inducted in the study. Intralesional / peri-lesional Interferon(IFN) Alpha-2b was given to the patients weekly along with interferon Alpha-2b topical drops four times daily, for Three 03 months. These patients were followed in Out Patient Department of respective hospitals and examined. For resolution or recurrence of lesion for at least three (03) months. And final results were compiled. Results: Study was conducted at Mayo Hospital Lahore, Armed Force institute of Ophthalmology, Rawalpindi and Lahore General Hospital, Lahore. Total Sample size of 90 (Ninety) Patients is estimated by using 95% confidence level, 10% absolute precision with expected percentage of Ocular surface squamous neoplasia as 91.6%. n= (Z1-?/2)2 X P X q / d2 Z1-?2 = Confidence level 95% = 1.96 P = Prevalence 91.6% q= 1-P d= Absolute precision 10% Out of these Twenty-nine, 29 were females and Fifty Nine, 59 were male patients. Non-Probability consecutive sampling was done. All patients tolerated and responded well to the treatment. There was recurrence in Eight 8 eyes. Conclusion: For the management of Ocular surface squamous Neoplasia IFN alpha 2 b is safe and effective choice with low recurrence rates.